Probation of ocupational therapy in the family health program: reflections about a didatic-assistential parnership between the reata/USP and the PSF/QUALIS-SP - Rocha, Eucenir Fredini; Shimizu, Priscila Narimoto; Barrales, Lorena Martinez (Revista de Terapia Ocupacional da Universidade de São Paulo, 2002)
According to the most recent proposals of health attention and rehabilitation of the disable people, in 2001 the Occupational Therapy course at the Medical School of University of São Paulo started to offer a trainee program, in partnership with PSF - Programa de Saúde da Família /QUALIS (Family Health Care Program /QUALIS) - Zerbini Foundation, of the São Paulo borough - Southeast area, to the students of 7th and 8th semesters. This experience has been proportioning to the students the opportunity to articulate the theoretical foundations with the practical acting with the handicapped population. The results have been beneficial to the students, to the clients and also to the academy. The students benefit from the professional training in public health, in the basic care network, with the other teams (family health care, oral health, mental health and specialists). The clients are benefited from the attention focused on their needs, in the area of their homes and the academy enriches by allowing a critical attitude towards the structure of the trainee program, capable of glimmering beyond the reductionist medical organicist principles. In order to respond to the interests and needs of the disable patients, the Occupational Therapy trainee program, in partnership with PSF - QUALIS, bases on the inclusion principles and on actions that seek the dismantle of the social exclusion. The various kinds of attention offered are focused on the needs of the person, the group and the community, based on the connected territory. All the actions seek the conquest of the autonomy and independence of the handicapped person, through the development of their personal capacity of making their own decisions and assuming their life control.